((x)/2012)+((x+1)/2013)+((x+2)/2014)+((x+3)/2015)+((x+4)/2016)=5 09/07/2021 Bởi Arya ((x)/2012)+((x+1)/2013)+((x+2)/2014)+((x+3)/2015)+((x+4)/2016)=5
Đáp án: x=2012 x/2012x2012+ x+1/2013x+1/2013 +x+2/2014x+2/2014 +x+3/2015x+3/2015 +x+4/2016x+4/2016 =5 =>x/2012x2012+ x+1/2013x+1/2013 +x+2/2014x+2/2014 +x+3/2015x+3/2015 +x+4/2016x+4/2016 -5=0 =>(x//2012x2012-1)+ (x+1/2013x+1/2013-1) +(x+2/2014x+2/2014-1) +(x+3/2015x+3/2015-1) +(x+4/2016x+4/2016 -1)=0 =>x−2012/2012x−2012/2012+ x−2012/2013x−2012/2013 +x−2012/2014x−2012/2014 +x−2012/2015x−2012/2015 +x−2012/2016x−2012/2016 =0 =>(x-2012)(1/20121/2012+ 1/20131/2013 +1/20141/2014 +1/20151/2015 +1/20161/2016)=0 =>x-2012=0 ( vì 1/20121/2012+ 1/20131/2013 +1/20141/2014 +1/20151/2015 +1/20161/2016 >0) =>x=2012 Bình luận
Đáp án: x=2012 Giải thích các bước giải: $\frac{x}{2012}$+ $\frac{x+1}{2013}$ +$\frac{x+2}{2014}$ +$\frac{x+3}{2015}$ +$\frac{x+4}{2016}$ =5 =>$\frac{x}{2012}$+ $\frac{x+1}{2013}$ +$\frac{x+2}{2014}$ +$\frac{x+3}{2015}$ +$\frac{x+4}{2016}$ -5=0 =>($\frac{x}{2012}$-1)+ ($\frac{x+1}{2013}$-1) +($\frac{x+2}{2014}$-1) +($\frac{x+3}{2015}$-1) +($\frac{x+4}{2016}$ -1)=0 =>$\frac{x-2012}{2012}$+ $\frac{x-2012}{2013}$ +$\frac{x-2012}{2014}$ +$\frac{x-2012}{2015}$ +$\frac{x-2012}{2016}$ =0 =>(x-2012)($\frac{1}{2012}$+ $\frac{1}{2013}$ +$\frac{1}{2014}$ +$\frac{1}{2015}$ +$\frac{1}{2016}$)=0 =>x-2012=0 ( vì $\frac{1}{2012}$+ $\frac{1}{2013}$ +$\frac{1}{2014}$ +$\frac{1}{2015}$ +$\frac{1}{2016}$ >0) =>x=2012 Bình luận
Đáp án:
x=2012
x/2012x2012+ x+1/2013x+1/2013 +x+2/2014x+2/2014 +x+3/2015x+3/2015 +x+4/2016x+4/2016 =5
=>x/2012x2012+ x+1/2013x+1/2013 +x+2/2014x+2/2014 +x+3/2015x+3/2015 +x+4/2016x+4/2016 -5=0
=>(x//2012x2012-1)+ (x+1/2013x+1/2013-1) +(x+2/2014x+2/2014-1) +(x+3/2015x+3/2015-1) +(x+4/2016x+4/2016 -1)=0
=>x−2012/2012x−2012/2012+ x−2012/2013x−2012/2013 +x−2012/2014x−2012/2014 +x−2012/2015x−2012/2015 +x−2012/2016x−2012/2016 =0
=>(x-2012)(1/20121/2012+ 1/20131/2013 +1/20141/2014 +1/20151/2015 +1/20161/2016)=0
=>x-2012=0 ( vì 1/20121/2012+ 1/20131/2013 +1/20141/2014 +1/20151/2015 +1/20161/2016 >0)
=>x=2012
Đáp án:
x=2012
Giải thích các bước giải:
$\frac{x}{2012}$+ $\frac{x+1}{2013}$ +$\frac{x+2}{2014}$ +$\frac{x+3}{2015}$ +$\frac{x+4}{2016}$ =5
=>$\frac{x}{2012}$+ $\frac{x+1}{2013}$ +$\frac{x+2}{2014}$ +$\frac{x+3}{2015}$ +$\frac{x+4}{2016}$ -5=0
=>($\frac{x}{2012}$-1)+ ($\frac{x+1}{2013}$-1) +($\frac{x+2}{2014}$-1) +($\frac{x+3}{2015}$-1) +($\frac{x+4}{2016}$ -1)=0
=>$\frac{x-2012}{2012}$+ $\frac{x-2012}{2013}$ +$\frac{x-2012}{2014}$ +$\frac{x-2012}{2015}$ +$\frac{x-2012}{2016}$ =0
=>(x-2012)($\frac{1}{2012}$+ $\frac{1}{2013}$ +$\frac{1}{2014}$ +$\frac{1}{2015}$ +$\frac{1}{2016}$)=0
=>x-2012=0 ( vì $\frac{1}{2012}$+ $\frac{1}{2013}$ +$\frac{1}{2014}$ +$\frac{1}{2015}$ +$\frac{1}{2016}$ >0)
=>x=2012